APOE and COMT polymorphisms are complementary biomarkers of status, stability, and transitions in normal aging and early mild cognitive impairment - Dixon, Roger A.; DeCarlo, Correne A.; MacDonald, Stuart W. S.; Vergote, David; Jhamandas, Jack; Westaway, David (Frontiers in Aging Neuroscience, 2014)
Objective: Research has reported associations among selected genetic susceptibility biomarkers and risk of (a) normal cognitive aging decrements, (b) established mild cognitive impairment (MCI), and (c) sporadic Alzheimer’s disease (AD). In focusing on the transitional normal-to-early MCI phase, we examine associations among three theoretically relevant polymorphisms (APOE [rs429358, rs7412], BDNF [rs6265], COMT [rs4680]) and both baseline cognitive status (MCI versus normal aging) and two-wave (four-year) longitudinal stability or change profiles. The latter included three profiles: (a) stable as normal aging, (b) stable or chronic impairment (MCI-to-MCI), and (c) emergence of impairment (normal-to-MCI). Method: Genotyped older adults (n = 237 at baseline; age range = 64-91; 62% women) from the Victoria Longitudinal Study were examined for (a) independent and interactive associations of three genetic polymorphisms with (b) two objectively classified cognitive status groups (not-impaired controls (NIC) and MCI) at (c) both baseline and across a two-wave (four-year) longitudinal interval. Results: First, logistic regression revealed that the presence of at least one APOE ε4 allele (the risk factor for AD) was linked to greater baseline risk of objective MCI. Second, multinomial logistic regression revealed that (a) the presence of an APOE ε4 allele was associated with an increased risk of 4-year MCI status stability (chronicity), and (b) the COMT homozygous risk genotype (G/G or Val/Val) was associated with an increased risk of both MCI-to-MCI stability (chronicity) and emerging NIC-to-MCI conversion. Discussion: Both chronicity and emergence of objectively classified early cognitive impairment may be genetically heterogeneous phenomena, with influences from a panel of both normal cognitive aging (COMT) and AD-related (APOE) polymorphisms.